2009
DOI: 10.1007/s11259-009-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the immune state of dogs suffering from pituitary gland dependent hyperadrenocorticism by determining changes in peripheral lymphocyte subsets

Abstract: In order to evaluate the immune state of dogs suffering from pituitary-dependent hyperadrenocorticism (PDH), peripheral lymphocyte subsets were examined. Twenty seven PDH dogs and eight healthy control dogs were used in the current study. Eight healthy dogs served as the control group. Twenty seven PDH dogs were categorized into 4 groups based on their post serum cortisol concentrations by ACTH stimulation test: 2-5, excellent control (n = 8); 5-20, fair control (n = 7); >20, poor control (n = 4); and untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Dogs with GBM have a high incidence of concurrent hyperadrenocorticism, hypothyroidism, and hyperlipidemia . These metabolic disturbances cause immune dysregulation in various species and may contribute to the development of, or magnify, cholecystitis (infectious and sterile) in dogs with GBM . Alternatively, it has been suggested that GBMs in dogs may be a consequence of primary chronic cholecystitis .…”
Section: Discussionmentioning
confidence: 99%
“…Dogs with GBM have a high incidence of concurrent hyperadrenocorticism, hypothyroidism, and hyperlipidemia . These metabolic disturbances cause immune dysregulation in various species and may contribute to the development of, or magnify, cholecystitis (infectious and sterile) in dogs with GBM . Alternatively, it has been suggested that GBMs in dogs may be a consequence of primary chronic cholecystitis .…”
Section: Discussionmentioning
confidence: 99%
“…Studies available describe immune status by means of peripheral lymphocyte subsets in dogs with cancer, 6,11,14,17 hyperadrenocorticism, 10 leishmaniosis, 1,9 or ehrlichiosis. 8,16 The data presented in the current study showed that immunophenotype of peripheral blood lymphocytes in diseased dogs may be altered.…”
mentioning
confidence: 99%
“…Glucocorticoid-induced insulin resistance is mediated by reduced cellular insulin signaling [2,3,11]. A cortisol concentration (after 1 hr ACTH-stimulation) of 2-5 µg/dl, via drug treatment, in CS dogs is considered to be an excellent control state [17]. However, cortisol concentrations, in our 4 dogs suffering from CS, were higher than those of the excellent control level range.…”
mentioning
confidence: 66%
“…A cortisol concentration of>20 µg/dl in the sample, obtained 1 hr after ACTH administration, was considered abnormal and consistent with CS. In addition, the adrenal glands were examined using ultrasound (Vivid 7, GE Yokokawa Medical System, Tokyo, Japan), and pituitarydependent hyperadrenocorticism was confirmed on the basis of a bilateral symmetric appearance or bilateral enlargement of the adrenal glands (minor axis; over 6-7 mm) [17]. All CS dogs were treated with trilostane (Adrestane, Kyoritsu Seiyaku Corporation, Tokyo, Japan) or mitotane (Opeprim, Yakuruto Honsha Co., Ltd., Tokyo, Japan) ( Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation